Zinc regulates reactive oxygen species generation in platelets. (3rd April 2021) - Lopes-Pires, M.E.; Ahmed, N. S.; Vara, D.; Gibbins, J. M.; Pula, G.; Pugh, N.
Abstract: Vascular complications resulting from atherosclerosis development are a major cause of death. Reactive oxygen species (ROS) are produced by platelets during activation, and have been demonstrated to positively regulate platelet activatory responses. Zn 2+ is also an important hemostatic cofactor in platelets, acting both as a platelet agonist and second messenger. Whilst the effect of Zn 2+ -dependent signaling mechanisms on ROS production in nucleated cells has been demonstrated, comparable roles in platelets have yet to be investigated. In this study we investigated the relationship between fluctuations in cytosolic Zn 2 [Zn 2+ ]i and platelet ROS production. Agonist-evoked ROS production, GSH levels and GPx activity are abrogated in platelets treated with the Zn 2+ -chelator, TPEN. Conversely, increasing platelet [Zn 2+ ]i using Zn 2+ ionophores potentiated ROS generation and decreased GSH levels and GPx activity. Zn 2+ -dependent ROS production was sensitive to pretreatment with DPI or mitoTEMPO, NADPH oxidase and mitochondria inhibitors respectively. Increasing [Zn 2+ ]i resulted in increases of Erk1/2 and JNK phosphorylation. Our data are consistent with a functional association between [Zn 2+ ]i and ROS production in platelets that could influence thrombus formation in a clinical context.